Local radio and health awareness which relation? - belblidia, fatiha nour elhouda (Journal of Social Sciences and Humanities, 2024)
Today, the mass media play an important role in the life of the individual and the society, and due to its status, it has received great care and attention from many studies that seek the role of the latter and its effectiveness in the development of societies Thus, local radio is considered one of the important and effective pillars on which to educate the local audience, down to its privacy,to achieve the desired goal in directing it to acquire sound health practices.